A review of scientific research in defensive cyberspace operation tools and technologies. Issue 1 (2nd January 2019) - Goethals, Paul L.; Hunt, Meghan E.
ABSTRACT: The realm of cybersecurity is perhaps one of the most quickly evolving areas within today's research space. New and emerging technologies, as well as the growth of cybersecurity environment, are affecting how the problem is oriented and framed by practitioners, analysts, and scientists. In previous reviews of cybersecurity research tools and methodologies, the focus has been primarily at the system, and in some cases sub-discipline level. From a macroscopic perspective, however, the facets of cybersecurity research are tied to one another in different ways – gaps within one area of the science may affect progress in other areas. In order to provide an overarching examination of the literature, deliver the most current status of cybersecurity research, and outline areas where scientific inquiries may have the greatest impact, a review of relevant research in cybersecurity tools and technologies is performed. The study is organized according to both active and passive Defensive Cyberspace Operations, which accounts for the bulk of the cyber research literature over the last two decades. Where it is a apparent, trends, challenges, and opportunities for research are noted across the cybersecurity landscape.